Phenotypic features of black and red dairy cattle populations in the Siberian region - Trotsenko Irina (EDP Sciences, 2021)
The surveys have identified features of the exterior for 742 breeding cows of black-motley and red steppe breed in the Omsk region conditions. It was found that black motley cows are larger than peers of the red steppe breed are; these differences are 4.7 cm in height at the withers, 8.3 cm - in chest circumference, 1.4 cm and 5.6 cm - in width at the shoulders and ischial tubercles respectively. The studying animals received 83–84 points for the general type of development, which corresponds to the assessment “B+”. The average daily milk yield of black motley cows was 24.1 kg with an average milk flow rate of 2.24 kg / min. Red steppe cows' average daily milk yield is lower by 2.0 kg and it is about 22.1 kg, the milk flow rate is lower by 0.36 kg / min than for cows of the black motley breed. Phenotypic features of the two cows’ dairy cattle populations of the Siberian region characterize it like animals with the correct exterior, severe forms of milk and able to exhibit a high milk productivity in the conditions of modern milk production technologies. Phenotypic exterior evaluation of the broodstock reveals all the necessary provisions for potentially high-yielding offspring.